The effects of corporate governance mechanisms on corporate performance in Jordan : The moderating role of enterprise risk management and ownership concentration - Saddam Shatnawi (Universiti Sains Islam Malaysia, 2024)
Jordanian economy is still suffering from recession aftermath and slow economy growth due to poor corporate governance (CG) practices, internal corruption issues, corporate financial crises, corporate security issues, high ownership concentration, and wars in the neighboring nations. The key purpose of this study is to investigate the relationship between board of directors (BoD), audit committee (AC) characteristics, enterprise risk management (ERM), ownership concentration (OC), and corporate performance. Overall 76 panel data were used, which were obtained from published annual reports of industrial and service sectors from Amman Stock Exchange from 2009 to 2017. A fixed effect model was used test various hypotheses of the study. Both accounting-based (ROA and ROE) and market-based (Tobin's Q) performance measures were tested. The findings showed the relationships between board director effectiveness and corporate performance ROA and ROE are significant for number of women in the board, board size, and board independence. Board meetings and Muslim directors in the board have insignificant effect on ROA and ROE. The AC size, AC meetings, AC independence, and accounting expertise in AC have significant positive relationship with ROA and ROE. Muslim director in AC has positive but insignificant relationship with ROA and ROE. Concerning relationship with Tobin’s Q, the findings showed that women in the board, board size, and board meeting have significant relationship with Tobin’s Q. Conversely, board independence and Muslim directors in the board has insignificant relationship with Tobin’s Q. Moreover, the findings showed that the AC independence, AC size, and the accounting expertise in AC have significant positive relationship with Tobin’s Q. However, AC meetings and Muslim director in AC have insignificant positive relationship with Tobin’s Q. The findings showed that ERM positively moderated the relationship between BDE on ROA, ROE, and Tobin’s Q. The findings also showed that ERM positively moderated the effect of ACE on ROA and ROE. The OC has a positive direct effect on ROA and ROE as well as a negative direct effect on Tobin’s Q. The results of this study could be useful to regulators in their attempts to improving corporate performance and enhance the quality of monitoring mechanisms, especially in an environment where the capital market is still evolving and the legal protection and law enforcement are weak.